DA Negatively Regulates IGF-I Actions Implicated in Cognitive Function via Interaction of PSD95 and nNOS in Minimal Hepatic Encephalopathy - Ding, Saidan; Zhuge, Weishan; Wang, Xuebao; Yang, Jianjing; Lin, Yuanshao; Wang, Chengde; Hu, Jiangnan; Zhuge, Qichuan (Frontiers in Cellular Neuroscience, 2017)
Insulin-like growth factor I (IGF-I) has been positively correlated with cognitive ability. Cognitive decline in minimal hepatic encephalopathy (MHE) was shown to be induced by elevated intracranial dopamine (DA). The beneficial effect of IGF-I signaling in MHE remains unknown. In this study, we found that IGF-I content was reduced in MHE rats and that IGF-I administration mitigated cognitive decline of MHE rats. A protective effect of IGF-I on the DA-induced interaction between postsynaptic density protein 95 (PSD95) and neuronal nitric oxide synthase (nNOS) was found in neurons. Ribosomal S6 protein kinase (RSK) phosphorylated nNOS in response to IGF-I by recruiting extracellular signal-regulated kinase (ERK1/2). In turn, DA inactivated the ERK1/2/RSK pathway and stimulated the PSD95–nNOS interaction by downregulating IGF-I. Inhibition of the interaction between PSD95 and nNOS ameliorated DA-induced memory impairment. As DA induced deficits in the ERK1/2/RSK pathway and the interaction between PSD95 and nNOS in MHE brains, IGF-I administration exerted a protective effect via interruption of the interaction between PSD95 and nNOS. These results suggest that IGF-I antagonizes DA-induced cognitive loss by disrupting PSD95–nNOS interactions in MHE.